2018
DOI: 10.1016/j.synbio.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of precursor amino acid supplies for improving bacitracin production by activation of branched chain amino acid transporter BrnQ and deletion of its regulator gene lrp in Bacillus licheniformis

Abstract: Bacitracin, a new type of cyclic peptide antibiotic, is widely used as the feed additive in feed industry. Branched chain amino acids (BCAAs) are the key precursors for bacitracin synthesis. In this research, soybean meal was served as the raw material to supply precursor amino acids for bacitracin synthesis, and enhanced production of bacitracin was attempted by engineering BCAA transporter BrnQ and its regulator Lrp in the bacitracin industrial production strain Bacillus licheniformis DW2. Firstly, our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Here, Leu, derived from pyruvate, acted as the initial precursor for pulcherriminic acid synthesis. Because of the low concentration of intracellular Leu in B. licheniformis DW2 (27), Leu supply might be a bottleneck for pulcherriminic acid production. Vogt et al (28) have obtained an efficient L-Leu production strain of Corynebacterium glutamicum by removing the feedback resistance and deleting the repressor LtbR for L-Leu synthesis, and Leu yield was increased to 24 g/liter under optimized fed-batch fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, Leu, derived from pyruvate, acted as the initial precursor for pulcherriminic acid synthesis. Because of the low concentration of intracellular Leu in B. licheniformis DW2 (27), Leu supply might be a bottleneck for pulcherriminic acid production. Vogt et al (28) have obtained an efficient L-Leu production strain of Corynebacterium glutamicum by removing the feedback resistance and deleting the repressor LtbR for L-Leu synthesis, and Leu yield was increased to 24 g/liter under optimized fed-batch fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Vogt et al (28) have obtained an efficient L-Leu production strain of Corynebacterium glutamicum by removing the feedback resistance and deleting the repressor LtbR for L-Leu synthesis, and Leu yield was increased to 24 g/liter under optimized fed-batch fermentation. In addition, Zhu et al (27) improved the accumulation of intracellular branched-chain amino acids (BCAAs) by overexpressing the BCAA importer BrnQ, which led to a 22.4% increase in the bacitracin yield. In our work, the concentration of intracellular Leu was increased by 227.6% via overexpressing ilvBHC-leuABCD and deleting bkdAB, and a 49.0% increase of pulcherriminic acid yield was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Since soybean meal contains Met , overexpression of MetP improved the accumulation of intracellular Met, which further benefit bacitracin production. Meantime, several other amino acid transporters (YdhG, BrnQ, and LysE) have also been engineered for bacitracin production (Li et al, 2018;Zhu et al, 2018;Wu et al, 2019), indicated that engineering amino acid transporter was an efficient strategy for bacitraicn production. Similar to Met transportation, several other amino acids also have multiple corresponding transporters.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic pathways of Lysine (Lys) and Ornithine (Orn) were strengthened, which led to 28.95 and 16.5% increases of bacitracin yields, respectively (Wu et al, 2019;Yu et al, 2019). BCAA transporters BrnQ and YdhG were engineered to improve intracellular BCAA accumulations for bacitraicn synthesis (Li et al, 2018;Zhu et al, 2018). Additionally, the main regulators in carbon, nitrogen and phosphorus metabolisms were engineered, which led to a 35.72% increase of bacitraicn yield (Cai et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids, especially BCAAs, are often used in the antibiotics production. It was reported that enhancement of precursor amino acid supplies improved bacitracin production by activation of branched chain amino acid transporter BrnQand deletion of its regulator gene lrp in Bacillus licheniformis [36]. BCAAs were used in improving secondary metabolites of Streptomyces spp, for example bitespiramycin [37].…”
Section: Discussionmentioning
confidence: 99%